Characterization Of Honey As Active Thin Film For Resistive Switching Memory Applications - Seah, Ying Zhi (Universiti Sains Malaysia, 2022)
Bio-organic resistive switching (RS) device was gaining more attention due to von Neumann bottleneck and electronic waste issue. Research on honey to be act as active thin film in RS device was mainly on electrical properties. The aim of this research is to investigate the thermal effects towards chemical structure and composition of honey in controlling the resistive switching properties of honey thin film. Different concentration (0, 10, 20, 30, 40 and 50 wt.%) of honey solution was characterized by goniometer, fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). 30 wt.% honey solution was spin coated onto 20mm × 20mm ITO glass slide and dried at different drying temperature (100, 120, 140, 160°C) and time (6, 9, 12, 15 hours). FTIR, optical microscope, atomic force microscopy (AFM), scanning electron microscope (SEM) and semiconductor parameter analyzer (SPA) was used to characterize the solidified honey film. By considering the solubility of honey, 30 wt.% honey solutions with contact angle of 44.42° was chosen for subsequent experiment. Endothermic reactions occur due to dehydration, melting, caramelization and Maillard reaction in honey mixture and causes chemical structural changes in honey which the O-H bond decreases along the heating. The honey has a good coverage on ITO glass slide and the film was relatively uniform and flat as the average roughness was around 0.5424-2.439nm except for honey dried at 100°C for 6h. The Au/Pd/honey/ITO test device shows analogous switching with multilevel I-V characteristic that benefits artificial synapse applications. Lastly, honey dried at 100°C for 12h shows the best resistive switching properties due to high ON/OFF ratio of 1.322 at 0.25V.